Valuation of small farms - Bouma, M.B.; Linker, P.J. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
61 pág, ilus, tab, 6 ref. También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 116